Growth response of lobster panulirus homarus reared in tanks and in floating net cages fed with compound and fresh feed - Giri, Nyoman Adiasmara; Irvin, Simon; Haryanti; Sudewi; Selamat, Bejo; Jones, Clive M.; Mujiono (Penerbit Universiti Kebangsaan Malaysia, 2023)
Feeding efficiency is an important factor that supports the success of lobster grow-out culture. This study aimed to investigate growth of different sex of lobsters after being fed with combination of compound and fresh feed in indoor tanks (experiment-1) and growth of male lobster fed with different co-feeding diets in net floating cages (experiment-2). In experiment-1, five replicates of ten lobsters (191.1 ± 18.1 g) for each different sex (i.e., all males, males and females, and all females) were reared in 2 × 2 × 1 m3 tanks with flow through water system and fed with combination of compound (75%) and fresh feed (25%) for 120 days. In experiment-2, four replicates of 20 all male lobsters (183.6 ± 17.6 g) were reared in 12 net cages of 2 × 2 × 2.5 m3 and were fed with compound feed only, compound feed (75%) and fresh feed (25%), and compound feed (75%) with mussel meat (25%) for 120 days. Experiment-1 showed that growth (quantified as weight gain) of all male lobsters was the highest (59.4 ± 10.0 g). Experiment-2 showed that compound feed combined with fresh feed resulted in higher growth of lobster (0.73 ± 0.17 g) than 100% compound feed. There was no difference in survival rate of lobster among the treatment in both experiments with 94 – 100% in experiment-1 and 75.2 to 85.0% in experiment-2. The mortality of lobster caused by Milky Hemolymph Disease (MHD) in floating cage was found higher than in indoor tanks.